Franchigie elevate e copertura assicurativa delle sperimentazioni cliniche (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Two insurance policies relating to experimental protocols examined by an ethics committee have very high deductibles (25,000 euros, the former; £ 25,000 the other). One of the two subordinates any payment to the injured person to the previous reimbursement of the deductible by the insured to the insurer. According to Italian law this clause is not admissible and such contracts with high deductibles are to be considered acceptable only if there is a clear guarantee that the insurance company will cover the damage regardless of the previous liquidation of the deductible. The peculiarity of a high deductible must however be explained to the patient before the trial and reported in the informed consent form.
Keywords: Ethics Committees; high deductibles; insurance coverage; experimental protocols; clinical trials